Health anxiety symptoms among Icelandic fibromyalgia patients and their impact on quality of life - Dagmar Ólafsdóttir 1985- (2017)
The prevalence of health anxiety is unknown in Iceland, but studies have indicated that the condition is relatively common in secondary healthcare in other countries. This pilot study was conducted to examine the prevalence of health anxiety among Icelandic fibromyalgia patients seeking service at Þraut, center of fibromyalgia and related conditions in Iceland. This is a data based study that used medical records from 92 individuals. The sample contains 86 females (93.5%) and 6 males (6.5%), ranging in age from 18 to 73 years old, with the mean age of 42.73 (SD = 12.13). The Short Health Anxiety Inventory (SHAI) was used to screen for health anxiety. High level of health anxiety was found in 44.9% of the individuals. Other findings from the study were that fibromyalgia patients that were screened with high level of health anxiety reported more severe fibromyalgia symptoms, lower quality of life and more fatigue. Also, higher percentage of FM patients with high health anxiety met criteria for psychiatric disorders compared to those with lower level of health anxiety. Keywords: health anxiety, hypochondriasis, fibromyalgia, quality of life. Tíðni heilsukvíða á Íslandi er óþekkt, en erlendar rannsóknir hafa sýnt fram á að kvillinn sé tiltölulega algengur á heilsugæslustöðvum og sérfræðiklíníkum. Þessi grunnrannsókn var gerð til þess að kanna tíðni heilsukvíða á meðal íslenskra vefjagigtarsjúklinga sem sækja sér þjónustu hjá Þraut, miðstöð vefjagigtar og tengdra sjúkdóma á Íslandi. Rannsóknin notaðist við upplýsingar úr sjúkraskrám Þrautar frá 92 einstaklingum. Úrtakið innihélt 86 konur (93,5%) og 6 karla (6,5%) þar sem aldursbilið var frá 18 til 73 ára. Meðalaldur úrtaksins var 42,73 (SF = 12,13). The Short Health Anxiety Inventory (SHAI) listinn var notaður til þess að skima fyrir heilsukvíða. Hár heilsukvíði fannst á meðal 44,9% einstaklinganna. Aðrar niðurstöður voru að þeir vefjagigtarsjúklingar sem skimuðust með háan heilsukvíða greindu einnig frá alvarlegri einkennum vefjagigtar, þeir skoruðu lægra á skala ...